nm23-H1 is a negative regulator of TGF-β1-dependent induction of epithelial–mesenchymal transition - Zhao, Rongzhi; Gong, Lei; Li, Lin; Guo, Lili; Zhu, Daxing; Wu, Zhihao; Zhou, Qinghua (Experimental cell research, 2013)
Members of transforming growth factor-β(TGF-β) family are the main inducers of epithelial–mesenchymal transition (EMT) during embryogenesis and cancer pathogenesis. However, a significant crosstalk between TGF-β and other signals occurs during the induction of EMT. nm23-H1 was the first metastasis suppressor gene to be identified on the basis of an inverse relationship between nm23-H1 expression and metastasis stage. Despite extensive studies, the mechanism underlying its ability to suppress metastasis is far from elucidated. We demonstrated here that the nm23-H1 negatively regulated TGF-β1-dependent induction of EMT in non-aggressive lung cancer cell line. nm23-H1 knockdown significantly enhanced TGF-β1-induced suppression of epithelial marker E-cadherin and upregulation of mesenchymal markers β-catenin and fibronectin. The invasive and migratory potential of lung cancer cells upon TGF-β1 treatment was also markedly enhanced by nm23-H1 knockdown. On the other hand, the effect of nm23-H1 depletion on TGF-β1-induced EMT was reversed by ectopic re-expression of shRNA-resistant nm23-H1 protein. Furthermore, TGF-β1-induced EMT potentiated by nm23-H1 depletion was partially dependent on transcriptional factor Snail expression. Finally, we found Src kinase is involved in regulation of TGF-β1-induced EMT by nm23-H1. Our results suggest a means of restoring nm23-H1 to suppress TGF-β1-induced EMT that may exploited therapeutically for the management of metastasis diseases. ► The metastasis suppressor nm23-H1 negatively regulated TGF-β1-induced EMT. ► TGF-β1-induced EMT potentiated by nm23-H1 depletion was dependent on Snail expression. ► Src kinase is involved in regulation of TGF-β1-induced EMT by nm23-H1.